Victims of (State) Terrorism: Human Rights Challenges in Indonesia - Prasetyo, Hery (Journal of Southeast Asian Human Rights, 2024)
The discussion of state power tends to elaborate on the problem of the legitimation of using force to deliver public goods. Seminal works by Machiavellian theoreticians stand on this argument and focus on developing a strong government that can control how the power works. There is a debate continuously elaborating on the nature of state power, mainly to present the humanist power relations; however, the problems of overuse of power and the fallen victims cannot wait until academia makes a consensus. With the various governmental models, the state has a complex issue, such as the nexus between the plurality of social identity and other categories attributed to the citizens, which becomes essential to overcome the problems of unpredictable enemies with the most efficient strategist. Following these backgrounds, it is crucial to enhance knowledge about the variety of the implementation of state power to control, supervise, and docile the citizens. In doing so, first, figuring the concept of terrorism with multiple interpretations, in which states play their strategy to raise public awareness while elevating the regime of terror by creating a common enemy. Secondly, how has the technology to govern, with a technicalization of specific indicators, been used to manage the risk and possibly minimize the number of victims. Lastly, concern about this condition leads to human rights fulfillment, particularly how the state's "conduct to conduct" can ensure citizens' well-being. As a point for reflection, this essay argues that state power has a paradox in delivering sovereignty; the challenge is how to construct social spaces that can reduce the overuse of power. Keywords: Governmentality, Human Rights, Power, State, Terrorism